IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS PROJECT BASED LEARNING DENGAN MEDIA APLIKASI CANVA UNTUK MEMBANGUN KREATIVITAS SISWA MTS. MATHOLIUL HUDA PUCAKWANGI PATI - Muhammad Fathul Mujib; Muhammad Imam Taqiyyuddin; Muhammad Vicky Yakhya; Dany Miftah M. Nur (ARIMA : Jurnal Sosial Dan Humaniora, 2024)
In today's education era, it is very necessary to develop learning models that build student creativity. One interesting method is Project Based Learning (PjBL) which emphasizes project-based learning and direct experience. Technology is also very important to be an integral part of learning. The purpose of this study is to build the creativity of MTs. Matholiul Huda Pucakwangi Pati students through social studies learning using the Project Based Learning learning model assisted by the Canva Application. This study involved classroom action research involving 32 class IX A students at MTs. Matholiul Huda Pucakwangi Pati. The study used qualitative descriptive which the author did at MTs. Matholiul Huda Pucakwangi Pati. From the author wants to obtain results that the implementation of the Project Based Learning learning model with Canva application media students to build creativity at Mts. Matholiul Huda Pucakwangi Pati effectively. Keywords: keywords, alphabetic ordered